Plasma Science and Technology - Shahzad, Aamir (IntechOpen, 2022)
Plasma science and technology (PST) is a discipline investigating fundamental transport behaviors, interaction physics, and reaction chemistry of plasma and its applications in different technologies and fields. Plasma has uses in refrigeration, biotechnology, health care, microelectronics and semiconductors, nanotechnology, space and environmental sciences, and so on. This book provides a comprehensive overview of PST, including information on different types of plasma, basic interactions of plasma with organic materials, plasma-based energy devices, low-temperature plasma for complex systems, and much more.